‘In-person and online’: Experiences of in-person instruction for UK secondary students during the 2020 pandemic - MacLeod, C (2022)
During the COVID-19 pandemic, the UK was one of the many countries around the world who kept schools open to provide in-person instruction for vulnerable pupils and the children of essential workers. Attendance of in-person instruction in the UK peaked at 17.5% in July of 2020 and most school leaders indicated that there were between 10 and 29 pupils attending in-person instruction. Yet, the experiences of students who attended school in-person have had comparatively little study and it has been assumed that their experiences were approximately similar to students attending online instruction from home. The aim of this research is to investigate the unique experiences of UK secondary students who attended school in-person during the COVID-19 pandemic. In particular, this study evaluates how the complex relationship between digital technology and the socio-spatial context of schools mediated students’ experiences of in-person instruction. Semi-structured interviews were conducted with twelve students in UK secondary schools. These interviews were then transcribed and coded for key themes. Overall, the students felt that being in-person provided them with more opportunities to socialize, form close relationships with friends and teachers, and access academic and socio-emotional support. However, some also struggled to gain a sense of normality at school due to the heightened regulatory environment, anxiety about coronavirus, and greater loss of autonomy over their own lives. In contrast to narratives of the ‘disruptive’ effect of education technology, students demonstrated a high level of agency over their use of digital technology and felt that they were able to quickly adapt to online remote instruction.